Implicaciones Psicológicas En Una Persona Con Enfermedad Huérfana, “Dermatopolimiositosis”. (2019)
This document refers to the psychological implications that are presented in a person who has been diagnosed with an orphan disease called dermatopolymyositis, based on this, it is intended to describe the emotional characteristics, affective qualities and particularities that occur in their self-esteem. In this way it can be understood what orphan diseases are, and how they are assumed. by a person who is affected by it, likewise the consequences that are generate at a psychological level in the patient who suffers from this entity, therefore it is necessary to carry out a theoretical review of this topic.